Waste discharge into the marine environment : principles and guideline for the Mediterranean action plan - Polytechnic of Milan Institute of Sanitary Engineering; World Health Organization. Regional Office for Europe; United Nations Environment Programme (New York : Pergamon Press., 1982)
10